KAJIAN POTENSI WIRAUSAHA KOMUNITAS PEMULUNG TPA AIR DINGIN KOTA PADANG (JURNAL ECONOMICA : Research of Economic And Economic Education, 2018)
This paper present about the study on the potential of entrepreneurship owned by scavengers community in an effort to improve the welfare of life to be better. This research is a qualitative research. The analytical approach used is descriptive analysis approach, whose purpose is to describe, explain or explain deeply about certain variables that exist in a society. Data collection using observation method, interview, documentation. The technique of selecting informants using purposive sampling. Informants in this research is scavenging community located around final disposal (TPA) Air Dingin, Padang City. The validation technique referred to the use of Lincoln and Guba standards of credibility, transferability, dependability, confirmability. The field findings that most of the scavengers are housewives who do not have the skills and reactivation, but have the spirit to have more results of the pulp that can be sold to agents or collectors even with low price. The entrepreneurship spirit they have is still passive, they just follow the existing habit by selling all the collected garbage directly to the dealer or collectors, however by they add a little innovation to the results of garbage collected such as process plastic waste into a variety of unique and interesting creations then the selling value will be increased, which means they will get additional income. For that there is a need subsequent review of the understanding of entrepreneurship and assessment of the type of skill that is appropriate for scavengers community in processing the results of the pulses that have added value. Key words: Scavengers community; entrepreneurship; and welfare improvement ABSTRAK Makalah ini merupakan hasil kajian tentang potensi entrepreneurship yang dimiliki oleh komunitas pemulung dalam upaya meningkatkan kesejahteraan hidup. Penelitian ini merupakan penelitian kualitatif. Pendekatan analisis yang digunakan adalah pendekatan analisis deskriptif, yaitu penelitian yang tujuannya untuk menguraikan, menerangkan atau menjelaskan secara mendalam tentang variabel tertentu yang ada dalam suatu masyarakat. Pengumpulan data menggunakan metode observasi, wawancara, dokumentasi. Teknik pemilihan informan menggunakan purposive sampling. Informan dalam penelitian ini adalah komunitas pemulung yang berada di sekitar Tempat Pembuangan Akhir (TPA) Air Dingin Kota Padang. Teknik menjamin keabsahan data mengacu kepada penggunaan standard dari Lincoln dan Guba yaitu credibility, transferability, dependability, confirmability. Hasil temuan dilapangan menunjukan bahwa  sebagian besar pemulung merupakan ibu-ibu rumah tangga yang tidak memiliki keahlian dan keterampilan, tetapi memiliki semangat untuk berusaha mendapatkan hasil pulungan yang dapat dijual kepada agen atau pengepul. Jiwa entrepreneur yang mereka miliki masih pasif, mereka hanya mengikuti kebiasaan yang telah ada yaitu menjual semua hasil pulungannya, seandainya mereka melakukan sedikit inovasi terhadap hasil pulungan seperti mengolah sampah plastik menjadi aneka kreasi yang unik dan menarik maka nilai jualnya akan meningkat yang berarti mereka akan mendapatkan income tambahan.  Untuk itu  diperlukan kajian berikutnya tentang pemahaman entrepreneur dan kajian jenis ketrampilan yang sesuai bagi komunitas pemulung dalam mengolah hasil pulungan yang memiliki nilai tambah.